New Rules of Refinancing and Investor Protection in China - Zhang, Yeyu; Zhang, Shangran; Zhu, Jianran (Journal of Management Policy and Practice, 2020)
This paper studies how the new rules of refinancing, which changed the pricing benchmark date of private placement to the approval date, influenced the impact of private placement on stock price. We find that the new rules of refinancing conveyed positive information to the market, making the announcement effect of approval date better. Meanwhile, the new rules significantly reduced the issuance discount rate and restrained the possible arbitrage behavior of major shareholders. For companies which pricing benchmark date was not the first day of the issuance, the market would form reasonable expectations of the issuance discount rate and it had a significant negative correlation with the announcement effect on the approval date. Our results show that the new rules improve the announcement effect of approval by decreasing the discount rate of private placement, and strengthen the protection of investors’ interests.